نفاذ القرارات الإدارية وسريانها في حق الأفراد - د. منير أحمد الشيباني (Aljameai, 2026)
المستخلص: يتناول هذا البحث مسألة نفاذ القرارات الإدارية وسريانها في مواجهة الأفراد، مميزًا بين النفاذ كعملية قانونية والتنفيذ كعمل مادي لاحق. يقرر أن القرار الإداري يكون نافذًا بالنسبة للإدارة من تاريخ صدوره، بينما لا يسري في حق الأفراد إلا من تاريخ علمهم به عبر النشر أو الإعلان أو العلم اليقيني، وهي الوسائل التي اعتمدها القضاء والمشرع لضمان حجية القرارات وفتح ميعاد الطعن عليها. كما يوضح أن إثبات وجود القرار يتم من خلال التوقيع والكتابة الرسمية والإعلانات والمراسلات والشهادات، مع تحميل عبء الإثبات على من يتمسك بالقرار.ويبرز البحث أن الاحتجاج بالقرار الإداري يرتبط بقدرة القرار على إحداث أثر قانوني تجاه المخاطبين به، وأن الإدارة ملزمة بإعلام الأفراد بمضمون قراراتها حتى يمكن مؤاخذتهم بأحكامها. ويؤكد أن العلم اليقيني يعد وسيلة معتبرة لسريان القرارات، شريطة أن يكون شاملاً لمحتويات القرار ومؤرخًا بشكل واضح.أما فيما يتعلق بمبدأ عدم رجعية القرارات الإدارية، فيؤكد البحث أنه قاعدة آمرة تستند إلى احترام الحقوق المكتسبة والمراكز القانونية الذاتية، بحيث لا يجوز المساس بها إلا بنص تشريعي صريح. ومع ذلك، يبين أن هناك استثناءات تشريعية وقضائية ترد على هذا المبدأ، تتيح للإدارة قدرًا من المرونة في ممارسة نشاطها بما يحقق المصلحة العامة دون الإخلال بمبدأ المشروعية.ويخلص البحث إلى أن التفرقة بين النفاذ والتنفيذ ضرورية لفهم الآثار القانونية للقرارات الإدارية، وأن تحديد لحظة النفاذ يمثل عنصرًا جوهريًا لضمان مشروعية الإجراءات اللاحقة واستقرار المراكز القانونية.Abstract:This research examines the enforceability of administrative decisions and their applicability to individuals, distinguishing between enforceability as a legal process and execution as a subsequent material act. It affirms that an administrative decision is enforceable for the administration from the date of issuance, while it binds individuals only from the moment they acquire knowledge of it through publication, notification, or certain knowledge—mechanisms recognized by legislation and jurisprudence to ensure validity and to open the period for appeal.The study clarifies that proof of a decision’s existence requires official documentation, signature, publication, correspondence, or testimony, with the burden of proof placed on the party invoking the decision. It emphasizes that the binding effect of an administrative decision lies in its capacity to generate legal consequences for those addressed, and that the administration is obliged to inform individuals of its content before holding them accountable. Certain knowledge is considered a valid means of enforceability, provided it is comprehensive, precise, and clearly dated.Regarding the principle of non-retroactivity, the research affirms its status as a mandatory rule safeguarding acquired rights and established legal positions, subject only to explicit legislative provision. Nonetheless, it acknowledges limited legislative and judicial exceptions that allow the administration flexibility to act in the public interest without undermining legality. Ultimately, the study concludes that distinguishing enforceability from execution is essential to understanding the legal effects of administrative decisions, and that identifying the precise moment of enforceability is critical to ensuring legality and stability of legal positions.